Content validity of the Japanese version of the health literacy and resiliency scale for youth with chronic illness - Sekine, Saya; Kobayashi, Kyoko; Ochiai, Ryota; Higaki, Takashi (Frontiers in Pediatrics, 2022)
Health literacy, which is the ability to find, understand, and use information as well as services to make informed health-related decisions and actions, is essential for ensuring that youths with chronic diseases adapt to and live with their illnesses. However, in Japan, an appropriate approach for measuring health literacy levels among children is yet to be developed. The Health Literacy and Resiliency Scale for Youth (HLRS-Y) was developed by Kathy Bradley-Klug and her colleagues to assess health literacy, resiliency, and self-advocacy/support among youths aged between 13 and 21 years with chronic illnesses in the United States of America (United States). In this study, we aimed to develop a Japanese version of the HLRS-Y and evaluate its content validity. After receiving approvals from the original authors, four nurse researchers with expertise in pediatric nursing translated the scale into Japanese (forward translation). Afterwards, the appropriateness of each expression was examined by a pediatrician. Next, an English native speaker translated the expressions into English (back-translation). We reported the back-translated version of the scale to the original authors to confirm its accuracy. The scale's content validity index (CVI) was evaluated by health professionals working in the fields of pediatric, transitional, and adult health care. The participants rated the items using a four-point scale. Each item was evaluated for a minimum item-level content validity index (I-CVI) value of 0.78. The scale's total and subscale validities were evaluated using a minimum scale-level content validity index based on an average (S-CVI/Ave) value of 0.90. Eleven participants responded to an online survey for evaluating content validity. Of the 36 items, 34 met the I-CVI criteria. Two items did not exceed the criteria's value, but they approximated it. The values of the S-CVI/Ave were 0.96, thereby satisfying the criteria's requirements. Based on the results, it was confirmed that the Japanese version of the HLRS-Y had good content validity. Future studies should examine the factor validity, known group validity, and reliability of this scale.